Measurement of the top-quark mass using a leptonic invariant mass in pp collisions at s $$ \sqrt{s} $$ = 13 TeV with the ATLAS detector. (Tufts University. Tisch Library., 2023)
Keywords : Hadron-Hadron Scattering, Top Physics.; Springer Open.